Career models in the new tripolar order. political profiles of the italian MPs after the 2022 general elections - Matteo Boldrini; Selena Grimaldi (QOE-IJES)
The 2022 general election confirmed the instability of the Italian political system and in its shift from a bipolar to a tripolar competition dynamic. The article explores similarities and differences among MPs elected in 2022 during such electoral turmoil, aiming to understand their profiles and career paths. Specifically, the research investigates whether certain elements such as gender and affiliation with an organisational thick or thin party may influence the MPs’ career models. We run a multinomial logistic regression to test the effects on multilevel career patterns by relying on an original dataset which comprises the socio-economic and political characteristics of the current MPS and their career trajectories for a total of 588 observations. Our findings show that women are often newcomers, and they are more likely to display an alternative career model. They struggle to fully capitalize on the opportunities offered by multilevel democracy, both before and after attaining their position as MPs. Furthermore, MPs belonging to a party with a strong organisation are more likely to develop unidirectional and integrated models, indicating their ability to navigate the multilevel context with well-planned and structured career paths.